A política sob o báculo: Dom Agostinho no comando da Diocese de Palmas - Francisco Beltrão (1970-2005) - Pongan, Pâmela (2019)
This dissertation aims to analyze the itinerary lived by Bishop Agostinho José Sartori, in the Southwest region of Paraná, in the context of concrete actions with an emphasis on the political dimension in the context of his Diocesan Church government, considering the fact that his episcopate was a the longest in the history of the Catholic Church in Brazil, based on political actions aimed at meeting the spiritual, social, cultural and economic needs of its faithful. Beginning with an analysis of the occupation and colonization process of the Southwest region of Paraná, highlighting the agrarian conflicts, divergences regarding borders and boundaries, migratory politics and popular religiosity that marked the conception of this region, discussing the transformations throughout history and the social construction that resulted in the current Southwest. Then, the arrival and institutionalization of the Catholic Church in the region was highlighted, emphasizing its actions to combat the existing popular religiosity, besides emphasizing the political actions taken by the Church throughout the conception of the Diocese of Palmas and its modifications until the arrival of the second Bishop Augustine José Sartori, main character of this research. By presenting his life history, and starting from an understanding of who he was, he set out to analyze his actions while at the head of the Diocese. This approach will be based on the analysis of documents such as pastoral letters, tomb books, newspaper articles and personal manuscripts of the bishop. During his 35 years of episcopacy, he went far beyond the spiritual, establishing relationships with regional and state leaders, seeking improvements in the region in several areas. Thus, it will be sought to identify and understand the influence of these actions in sudoestina society, in both political and social aspects, highlighting educational approaches, social communications, land issues and social issues, which directly affected the people of this region, results still felt today.